Factors Affecting Choice in A Multi-Stage Model: The Influence of Saliency and Similarity on Retrieval Set and the Implication of Context Effect on Consideration Set - Eric Santosa (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2009)
While it is considered a new paradigm in consumer research, the multi-stage model of consumer decision-making remains unclear as to whether brands are easily retrieved. Likewise, the process of consideration, after particular brands are successfully retrieved, is still in question. This study purports to investigate the effects of saliency and similarity on the ease of retrieval. In addition, referring to some studies of context effect, the effects of attraction, compromise, and assimilation are examined to observe whether they contribute to consideration. A within-subject design is employed in this study. Previously, three preliminary studies are arranged to determine the dominants, new entrants, attributes, and other criteria nominated in the experimental study. The results turn out to be supporting the hypotheses.